Only Winners in Tough Times Repeat: Hedge Fund Performance Persistence over Different Market Conditions - Sun, Zheng; Wang, Ashley W.; Zheng, Lu (Journal of Financial and Quantitative Analysis, 2018)
We provide novel evidence that hedge fund performance is persistent following weak hedge fund markets but is not persistent following strong markets. Specifically, we construct two performance measures, RET_DOWN and RET_UP, conditioned on the level of overall hedge fund sector returns. After adjusting for risks, funds in the highest RET_DOWN quintile outperform funds in the lowest quintile by approximately 7% in the subsequent year, whereas funds with better RET_UP do not outperform subsequently. The RET_DOWN measure can predict future fund performance over a horizon as long as 3 years, for both winners and losers and for funds with few share restrictions.